Menumbuhkembangkan Apresiasi Seni Rupa Anak Sekolah Dasar Terhadap Karya Seni Lukis Kaca Nagasepaha - I Gde Suryawan; Kadek Dwi Sentana Putra (STAHN Mpu Kuturan Singaraja, 2020)
Growing and developing applesisation is a form of solution for maintaining the sustainability of glass painting. To appreciate (to appreciate) means to appreciate. Respect means involving two things in the process, where the subject is the party that gives the award and the object of value is the party that is appreciated. This is where the importance of appreciating activities in art education is because students gain experience of absorbing, filtering, behaving, interpreting and responding to aesthetic symptoms in both works of art and nature. Having an attention process through the introduction of Nagasepaha glass painting to elementary school children will develop their experiences. Certain experiences that students have will certainly influence the point of their analysis of something, as well as in works of art. Keywords: Apretiation, Nagasepaha of Glass Painting